Correlation Between Adjuvant Chemotherapy Regimen, Recurrence Pattern and Prognosis of Cholangiocarcinoma After Radical Surgery - Rao, Le; Ma, Na; Liu, Yanli; Du, Lehui; Qu, Baolin (Frontiers in Oncology, 2022)
Background and purpose: About 70% of patients with radical surgery Cholangiocarcinoma (CCA) have recurrence and metastasis. There are few studies on the relationship between CCA adjuvant chemotherapy (mono or combined therapy), recurrence pattern (local, regional, distant recurrence) and prognosis [(Disease free survival, DFS), (Overall survival, OS)] after radical surgery. This study focuses on the correlation between CCA adjuvant chemotherapy, recurrence pattern and prognosis. Methods: The study involved retrospective analysis of data: preoperative hematology, clinical pathology, adjuvant chemotherapy regimens, recurrence pattern, DFS and OS, of 207 patients with CCA. Chi-square test was used to analyze the correlation between related factors and postoperative recurrence. Survival curves were plotted by Kaplan-Meier method, P-values were calculated by Log-rank for univariate analysis, multivariate COX regression method for multivariate analysis. Results：Using chi-square test, there were correlations between high carbohydrate antigen 19-9 level(CA19-9≥35), vascular invasion, single-agent adjuvant chemotherapy and postoperative recurrences (p=0.04, p=0.04, p=0.02), COX multivariate regression analysis showed that adjuvant chemotherapy (single vs. doublet drug regimen) was an independent prognostic factor for DFS (11.0 vs. 24.6 months, HR=2.88, P=0.01), whereas recurrence pattern (local vs. distant; regional vs. distant) was an independent prognostic factor for OS (31.2 months vs. 20.4 months, HR=0.58, p=0.01; 32.0 months vs. 20.4 months, HR=0.51, p=0.01). Conclusion：Adjuvant chemotherapy regimen was an independent prognostic factor of DFS, whereas recurrence patterns were independent prognostic factors for OS. adjuvant chemotherapy with doublet drug regimen is correlated with longer DFS, and different recurrence modes affect OS.